Flexible powder-free aerogel material as well as preparation method and application thereof
The flexible powder-free aerogel material prepared through crushing and mixing technology solves the fragility and powder loss problems of traditional aerogel materials in flexible and bendable applications, and achieves material preparation with high flexibility and good thermal insulation performance, which is suitable for insulation needs in a variety of dynamic environments.
Patent Information
- Application Number
- CN202411841752.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-13
- Publication Date
- 2025-03-21
- Estimated Expiration
- 2044-12-13
AI Technical Summary
Traditional aerogel materials have fragile, fragile and powder-loss problems in applications requiring flexibility and bendability, making it difficult to adapt to the insulation needs of energy storage equipment, special-shaped structures and dynamic environments.
Flexible powder-free aerogel materials are prepared using a combination of crushing and mixing. The specific steps include grinding the aerogel into powder particles and mixing it with the fiber, preparing the impregnation liquid and stirring it evenly with the mixture, and finally curing and forming it in the mold.
It achieves high flexibility, low thermal conductivity and good thermal insulation performance of the material. It is suitable for the insulation needs of curved and special-shaped structures, and has a simple and efficient process, which is suitable for large-scale production.
Smart Images

Figure BDA0005188123010000091
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of heat insulation material preparation technology, and in particular to a preparation method and application of a flexible powder-free aerogel material. Background Art
[0002] Traditional aerogel materials have extremely low thermal conductivity due to their unique nanoporous structure and are widely regarded as one of the best thermal insulation materials. They are usually made of materials such as silicon, metal oxides or organic polymers and are widely used in construction, aerospace, petrochemicals, automobile manufacturing and other fields. However, these aerogel materials often have some limitations, especially in situations where flexible and bendable applications are required. Traditional aerogel materials are usually fragile, brittle, lack flexibility, and are prone to powdering, which limits their use in some application scenarios that require bending, coating or shape adaptability.
[0003] With the development of technology, the market demand for flexible thermal insulation materials is growing, especially in energy storage devices, special-shaped structures and dynamic environments. Energy storage devices such as lithium batteries generate a lot of heat during operation, requiring effective thermal insulation and thermal management to ensure performance and safety. In addition, many modern industrial products and architectural designs tend to adopt streamlined and special-shaped structures, which require thermal insulation materials that can adapt to complex shapes. Therefore, the development of a new aerogel material that maintains the excellent thermal insulation properties of aerogel and has good flexibility is crucial to meet the needs of these emerging applications.
[0004] CN202110451418.4 provides an aerogel anti-corrosion and heat-insulating flexible board, which includes a core layer and a composite layer arranged on both sides of the core layer, wherein the composite layer includes a heat-conducting layer and an aerogel felt layer, and the heat-conducting layer and the aerogel felt layer are sequentially arranged in a direction away from the core layer; the aerogel felt layer is prepared by the following method: nano-silicon dioxide aerogel powder and polyurethane powder are mixed in a solvent, and an immersion liquid is obtained after stirring; aluminum silicate ceramic fiber felt is immersed in the immersion liquid to make the nano-silicon dioxide aerogel powder The gel powder particles and the polyurethane powder particles are immersed in the aluminum silicate ceramic fiber felt, and then the aluminum silicate ceramic fiber felt is taken out and dried at 50-80°C for 20-60 minutes; after hot pressing at 80-120°C and 3MP-10MP for 15-50 minutes, it is cooled to room temperature and the pressure is maintained for continuous pressing for 8-24 hours to form; the material of the core layer is chemically cross-linked polyethylene foam; the thermal conductive layer is a thermal conductive silicone sheet, one side of the thermal conductive silicone sheet is a frosted surface, and the frosted surface is connected to the aerogel felt layer. However, this aerogel composite material is made of multiple layers of materials, the interlayer strength is insufficient, and stratification problems are prone to occur during use; this method uses fiber felt as a reinforcing material, and there are problems such as insufficient material performance and insufficient plane accuracy caused by poor impregnation uniformity; the flexibility of the material also depends on the composite thermal conductive layer and core layer, and the shape depends on the shape of the fiber preform, which is not suitable for the manufacture of heterogeneous components; this method requires high temperature and high pressure curing conditions, has high equipment requirements, high cost, and is not easy to mass produce, which hinders the promotion and application of such materials.
[0005] The present invention aims to provide a flexible powder-free aerogel material and a preparation method thereof, which not only inherits the low thermal conductivity characteristics of traditional aerogels, but also has excellent flexibility and can adapt to various bending and wrapping requirements, especially in the insulation of energy storage equipment, protection of special-shaped structures and other fields requiring dynamic thermal management. Summary of the invention
[0006] In view of one or more technical problems existing in the prior art, the present invention provides a method for preparing a flexible powder-free aerogel material in a first aspect, the preparation method comprising the following steps:
[0007] (1) crushing and mixing raw materials: grinding the aerogel into aerogel powder particles, and then mixing the aerogel powder particles with fibers to prepare a mixed material;
[0008] (2) Preparation of impregnation solution: mixing an organic resin glue, a diluent solvent and a curing agent to obtain an impregnation solution;
[0009] (3) Mixing and impregnating: stirring the mixed material and the impregnating liquid uniformly to obtain a dispersed mixture;
[0010] (4) Curing and molding: placing the dispersed mixture into a mold for curing and molding to obtain the flexible aerogel material.
[0011] The second aspect of the present invention provides a flexible powder-free aerogel material prepared by the preparation method described in the first aspect of the present invention.
[0012] Compared with the prior art, the present invention has at least the following beneficial effects:
[0013] (1) The flexible powder-free aerogel material of the present invention has excellent flexibility and can meet the thermal insulation requirements of various curved and special-shaped structures. It is not as fragile, brittle and easy to fall off as traditional aerogel materials.
[0014] (2) The present invention uses fibers instead of fiber preforms (such as fiber felt) to directly mix with aerogel powder particles, thereby overcoming the problems of insufficient impregnation, long impregnation time, and high requirements for impregnation liquid in the prior art of impregnating fiber preforms with aerogel precursor solutions.
[0015] (3) The present invention optimizes the steps of crushing, mixing, impregnation and solidification, so that the method of the present invention has the advantages of simple process, high efficiency, large-scale production and cost reduction.
[0016] (4) The method of the present invention adopts a combination of crushing and mixing techniques to prepare aerogel materials, so that the prepared aerogel product has a more uniform particle distribution and a higher porosity, and better thickness accuracy, thereby providing better thermal insulation performance.
[0017] (5) The flexible powder-free aerogel material prepared by the method of the present invention has good flexibility, low thermal conductivity, good thermal insulation, high thickness accuracy, strong plasticity, no dust on the surface and high qualified rate of finished products. DETAILED DESCRIPTION
[0018] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0019] In a first aspect, the present invention provides a method for preparing a flexible powder-free aerogel material, the preparation method comprising the following steps:
[0020] (1) crushing and mixing raw materials: grinding the aerogel into aerogel powder particles, and then mixing the aerogel powder particles with fibers to prepare a mixed material;
[0021] (2) Preparation of impregnation solution: mixing an organic resin glue, a diluent solvent and a curing agent to obtain an impregnation solution;
[0022] (3) Mixing and impregnating: stirring the mixed material and the impregnating liquid uniformly to obtain a dispersed mixture;
[0023] (4) Curing and molding: placing the dispersed mixture into a mold for curing and molding to obtain the flexible aerogel material.
[0024] The present invention will be described in more detail below according to the steps.
[0025] Step (1): Crushing and mixing of raw materials
[0026] In this step, the aerogel is ground into aerogel powder particles, and then the aerogel powder particles are mixed with fibers to prepare a mixed material.
[0027] For example, the recovered aerogel blocks are crushed by a sand mill. As required, a predetermined mass of aerogel blocks can be placed in a sand mill, crushed to a desired particle size, and then the aerogel powder particles are mixed with the fibers.
[0028] In some preferred embodiments, the particle size of the aerogel powder particles can be controlled within the range of 1 μm to 100 μm. Finer particles can provide better flexibility and plasticity, and also help to improve the thermal insulation performance of the material. In some applications, such as where higher flexibility is required, the particle size may be further refined to the submicron level. For example, the low particle size can be controlled within the range of 1 to 50 μm (such as 1 μm, 10 μm, 20 μm, 30 μm, 50 μm), and particles in this particle size range can provide better flexibility and plasticity.
[0029] In other preferred embodiments, the particle size of the aerogel powder particles can be controlled to be 50 μm to 100 μm (for example, 60 μm, 70 μm, 80 μm, 90 μm, 100 μm). Particles in this particle size range can provide higher material strength and are suitable for aerogel material components that require compression strength.
[0030] The present invention has no particular restrictions on the types of aerogels and fibers, and common aerogels and fibers in the art can be used. For example, the aerogel can be silicon aerogel or carbon aerogel, etc.; the fiber can be quartz fiber or glass fiber, etc. Those skilled in the art can select as appropriate according to actual needs.
[0031] In the present invention, the length and diameter of the fiber may also affect the performance of the final aerogel material. Therefore, the length of the fiber is preferably 0.1 to 10 mm (for example, 0.1 mm, 0.5 mm, 1 mm, 3 mm, 5 mm, 10 mm). The diameter of the fiber can be 10 μm to 100 μm (for example, 10 μm, 20 μm, 30 μm, 40 μm, 50 μm, 60 μm, 80 μm, 100 μm) to ensure good dispersion and mechanical properties of the fiber in the aerogel matrix.
[0032] In some preferred embodiments, the weight ratio of the aerogel powder particles to the fibers in the mixture is 1:0.2-5, for example, 1:0.2, 0.5, 1, 2, 3, 4 or 5.
[0033] The present invention has no particular limitation on the type of aerogel, and for example, silicon aerogel or carbon aerogel may be used.
[0034] (2) Preparation of impregnation solution
[0035] In this step, the organic resin glue, the diluent solvent and the curing agent are mixed to obtain the impregnation solution.
[0036] For example, polyurethane glue or polyacrylate glue can be used as the organic resin glue, and then mixed with a diluent solvent and a curing agent. The mixing ratio can be, for example, 1:10~100:0.01~0.5 (for example, 1:10, 20, 50, 80 or 100:0.01, 0.05, 0.1, 0.2, 0.3, 0.4 or 0.5), thereby obtaining a glue with appropriate viscosity.
[0037] In the present invention, the viscosity of the impregnation liquid can be adjusted as required. Preferably, the viscosity of the impregnation liquid can be controlled to be 100 mPa·s to 20000 mPa·s for easy impregnation and molding, and the viscosity can be controlled within a sub-range thereof as required.
[0038] For example, the viscosity of the impregnation liquid can be controlled within a lower viscosity range, such as 100 to 1000 mPa·s (milliPascal seconds) (for example: 100 mPa·s, 200 mPa·s, 500 mPa·s, 800 mPa·s, 1000 mPa·s), which is more suitable for processes requiring higher fluidity and rapid impregnation molding.
[0039] For another example, the viscosity of the impregnating liquid can be controlled within a medium viscosity range, such as 1000 mPa·s to 10000 mPa·s (for example: 1200 mPa·s, 2400 mPa·s, 3600 mPa·s, 10000 mPa·s). This range can provide good fluidity and sufficient adhesion, and is more suitable for the impregnation molding process of most aerogels.
[0040] For another example, the viscosity of the impregnating liquid can be controlled within a high viscosity range, such as 10,000 to 20,000 mPa·s, which is more suitable for applications requiring higher bonding force and less fluidity to better maintain the stability of the aerogel structure.
[0041] The present invention has no particular limitation on the dilution solvent. For example, the dilution solvent can be selected from acetone, butanone, toluene, cyclohexanone, and the like.
[0042] The present invention has no particular restrictions on the curing agent and its dosage. You can select an appropriate curing agent (e.g., select a corresponding curing agent according to the organic resin glue used) and its corresponding dosage (e.g., select the required dosage according to the desired curing speed or curing time, i.e., the curing effective amount) as needed to adjust the curing time. For example, when using polyurethane glue, you can use curing agents such as triethylamine and stannous octoate; when using polyacrylate glue, you can use acrylic resin curing agent.
[0043] However, it should also be understood that the curing speed usually directly affects the efficiency of aerogel molding and the quality of the finished product. In particular, in the continuous production process, an appropriate curing speed can ensure that the product can be quickly cured after molding, reduce the production cycle, and improve production efficiency. Therefore, in some preferred embodiments, the mass ratio of the organic resin glue to the curing agent (i.e., the curing ratio) can be selected to be 1: (0.01-0.5), for example, 1: 0.02, 1: 0.1, 1: 0.3, or 1: 0.5.
[0044] (3) Mixed impregnation
[0045] In this step, the mixed material and the impregnating liquid are stirred evenly to obtain a uniformly dispersed mixed body.
[0046] In some preferred embodiments, the stirring speed can be controlled to be 30 rpm to 200 rpm, for example, 30 rpm, 50 rpm, 100 rpm, 150 rpm, or 200 rpm.
[0047] In the present invention, the stirring speed can ensure that the aerogel powder particles are evenly dispersed in the impregnation liquid while avoiding excessive shearing to cause particle damage. If the stirring speed is too low, sufficient mixing may not be achieved; and if the stirring speed is too high, it may cause particle breakage or degradation of the impregnation liquid.
[0048] In some preferred embodiments, the stirring temperature can be controlled to be 15°C to 35°C (e.g., 18°C, 20°C, 25°C, 35°C) to ensure the fluidity and reaction rate of the impregnation liquid. A lower temperature helps control the reaction rate, while a higher temperature can increase the fluidity of the impregnation liquid, but it is necessary to avoid exceeding the thermal stability limit of the glue solution.
[0049] In some preferred embodiments, the weight ratio of the mixed material to the impregnating liquid is 1:5-20.
[0050] In the present invention, the stirring temperature can ensure the fluidity and reaction rate of the impregnation liquid. A lower temperature helps to control the reaction rate, while a higher temperature can improve the fluidity of the glue solution, but it is necessary to avoid exceeding the thermal stability limit of the impregnation liquid.
[0051] (4) Curing and molding
[0052] In this step, the dispersed mixture is placed in a mold for curing and molding to obtain the flexible aerogel material.
[0053] This step is the key step to convert the impregnated mixed material (i.e., the dispersed mixture) into the final product. This step involves evenly placing the mixed material in a tooling or mold and curing it to give the aerogel a specific shape and size.
[0054] Generally, the curing temperature has a significant effect on the performance of the aerogel. In the present invention, the curing temperature is preferably 40°C to 80°C (e.g., 50, 60 or 70°C) to ensure that the cross-linking reaction of the impregnation solution can proceed sufficiently while avoiding thermal degradation of the material caused by excessively high temperatures.
[0055] The present invention has no particular limitation on the curing time. However, in some embodiments, the curing time may be 4 to 24 hours (eg, 4, 6, 12, 18 or 24 hours), and the surface is smooth and non-sticky after curing.
[0056] In some preferred embodiments, microwaves can be used to accelerate the curing process. Microwaves can quickly heat the material and promote the chemical reaction between the organic resin glue and the curing agent in the impregnation liquid, thereby shortening the curing time. In addition, curing molding assisted by microwaves (i.e., microwave curing molding) can achieve rapid curing at a lower temperature, thereby reducing energy consumption and production costs.
[0057] The present invention provides a flexible powder-free aerogel material in a second aspect. The material is prepared by the preparation method described in the first aspect of the present invention.
[0058] The flexible powder-free aerogel material of the present invention has excellent flexibility and can meet the thermal insulation requirements of various curved and special-shaped structures. The yield rate can reach more than 97%. The aerogel material prepared by the traditional method is often fragile and brittle and easy to lose powder (the powder loss not only leads to the reduction of the performance of the material itself, but also pollutes the use environment and there is a risk of accidents). By optimizing the crushing, mixing, impregnation and curing steps, the preparation process of the present invention is simple and efficient, and can achieve large-scale production and reduce costs.
[0059] In a third aspect, the present invention provides a use of the flexible powder-free aerogel described in the second aspect of the present invention in preparing materials or components (especially streamlined components or special-shaped components) for heat insulation or heat resistance purposes.
[0060] Example
[0061] In order to more clearly illustrate the technical solutions and advantages of the present invention, the present invention will be further described below in conjunction with embodiments.
[0062] It should be noted that the materials and reagents in the present invention can be directly purchased on the market or synthesized by themselves, and there is no limitation on the specific models.
[0063] Example 1
[0064] (1) crushing and mixing raw materials; grinding the recovered silica aerogel block by a sand mill, wherein 500 g of aerogel is placed in the sand mill, and after grinding to a desired particle size, the aerogel powder is mixed with quartz fiber (the mixing weight ratio of aerogel powder particles to fiber is 1:2) to obtain a mixture; the particle size is controlled to be 80 μm to 100 μm, the fiber length is 1 mm to 2 mm, and the diameter is 30 μm to 40 μm.
[0065] (2) Preparation of impregnation solution;
[0066] The polyurethane glue, acetone and triethylamine were mixed (the mixing weight ratio was 1:100:0.01) to obtain an impregnation liquid with a desired viscosity (about 500 mPa·s).
[0067] (3) Mixing and impregnation: The mixed material prepared in step (1) is mixed with the impregnation liquid prepared in step (2) (mixing weight ratio is 1:10) to form a dispersed mixture, and the stirring speed is set to 50 rpm and the stirring temperature is set to 20°C.
[0068] (4) Curing and molding: The dispersed mixture obtained in step (3) is placed in a cylindrical tooling for curing and molding, the curing temperature is 45°C, and the curing time is 20 hours. The internal mold surface is serrated (other shapes can be used as needed). After demolding, it is found that the product fits tightly with the equipment.
[0069] From grinding to demolding to obtain the finished product, the preparation method takes only 24 hours, which is three times more efficient than the traditional sol-gel process. The thickness tolerance of the obtained thermal insulation product is ±0.08mm, which is higher than the accuracy of the traditional product of ±0.2mm.
[0070] Example 2
[0071] (1) crushing and mixing raw materials; grinding the recovered silica aerogel block by a sand mill, putting 500 g of aerogel into the sand mill as needed, grinding to a desired particle size, and then mixing the aerogel powder with quartz fiber (the mixing ratio of aerogel powder particles to fiber is 1:2) to obtain a mixture; the particle size is controlled to be 10 μm, the fiber length is 1 mm to 2 mm, and the diameter is 30 μm to 40 μm.
[0072] (2) Preparation of glue solution;
[0073] Polyurethane glue, acetone and triethylamine were mixed (mixing weight ratio was 1:100:0.01) to obtain glue with required viscosity (viscosity was about 500 mPa·s).
[0074] (3) Mixing and impregnation: The mixed material prepared in step (1) is mixed with the impregnation liquid prepared in step (2) (mixing weight ratio is 1:10) to form a dispersed mixture, and the stirring speed is set to 50 rpm and the stirring temperature is set to 20°C.
[0075] (4) Microwave molding: The dispersed mixture obtained in step (3) is placed in a mold and cured under the assistance of microwaves (curing temperature is 60°C and curing time is 2 hours). After demolding, the product can fit tightly with the equipment.
[0076] From grinding to demolding to obtain the finished product, the operation time of this embodiment is only 6 hours, which is 16 times higher than the 96 hours of the traditional sol-gel operation and 4 times higher than that of Experimental Example 1. The thickness accuracy of the obtained product can be controlled within ±0.08mm.
[0077] Example 3
[0078] The method is basically the same as that of Example 1, except that the aerogel powder is mixed with quartz fiber (the mixing ratio of aerogel powder particles to fiber is 1:0.2). The resulting product has a lower density of about 100 kg / m 3 , suitable for thermal insulation of lightweight equipment.
[0079] Example 4
[0080] The method is basically the same as that of Example 1, except that the viscosity of the impregnation liquid is 5000 mPa·s, and the flat product is prepared. The density of the obtained product can reach 400 kg / m3, the overall surface is flat, and the anti-scouring performance is high.
[0081] Example 5
[0082] The process is carried out in substantially the same manner as in Example 2, except that the fibers used are aluminum silicate ceramic fibers, the density of the obtained flat plate is 300±20kg / m3, and the thickness accuracy (also referred to as "thickness tolerance") is ±0.1mm.
[0083] Comparative Example 1
[0084] The method is basically the same as that of Example 1, except that in step (1), the particle size of the aerogel powder particles is controlled to be 200 μm. It is found that when the particle size is greater than 100 μm, the product does not fit tightly with the equipment after demolding, the surface of the obtained product is rough, and the thickness accuracy is ±0.3 mm. Although the operation time is shortened, the product accuracy is reduced and does not meet the use requirements.
[0085] Comparative Example 2
[0086] The method is basically the same as that of Example 2, except that in step (2), the weight ratio of the polyurethane glue, acetone and curing agent is 1:5:0.01. It was found that when the ratio of the glue to the solvent was 1:5, the glue was too viscous (viscosity > 20000 mPa·s), the product did not fit tightly with the equipment after demolding, the finished glue was unevenly mixed, the thermal insulation performance decreased, and the product density was uneven (the density difference between the middle material and the surrounding materials of the product was as high as 40 kg / m 3 ).
[0087] Comparative Example 3
[0088] The method is basically the same as that of Example 1, except that the fibers are replaced by aluminum silicate ceramic fiber felt, and the polyurethane glue is replaced by polyurethane powder.
[0089] The aerogel powder particles obtained by grinding in step (1) are mixed with the polyurethane powder in the solvent to obtain an impregnation solution, and the aluminum silicate ceramic fiber felt is immersed in the impregnation solution, and then cured and formed. The molding process requires pressurization and heating. The overall molding time is 48 hours. Limited by the thickness accuracy requirements of the felt itself, the thickness accuracy of the obtained product is ±0.2mm.
[0090] Table 1. Properties of aerogel materials prepared in various embodiments and comparative examples (n=5)
[0091]
[0092] Note: Yield rate standard: thickness accuracy is no more than ±0.2mm or there is no visible damage on the surface.
[0093] It can be seen from the data of the embodiments and comparative examples that the method for preparing aerogel sheets of the present invention has a simple process and high efficiency, and can efficiently prepare flexible aerogel materials with a high pass rate; the aerogel material prepared by the present invention has high flatness and high thickness accuracy, with an error of no more than ±0.1 mm, and a yield rate of up to 97%, and the thickness accuracy and yield rate are significantly higher than those of comparative examples 1 to 3.
[0094] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some of the technical features therein. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A method for preparing a flexible powder-free aerogel material, characterized in that: The preparation method comprises the following steps: (1) crushing and mixing raw materials: grinding the aerogel into aerogel powder particles, and then mixing the aerogel powder particles with fibers to prepare a mixed material; (2) Preparation of impregnation solution: mixing an organic resin glue, a diluent solvent and a curing agent to obtain an impregnation solution; (3) Mixing and impregnating: stirring the mixed material and the impregnating liquid uniformly to obtain a dispersed mixture; (4) Curing and molding: placing the dispersed mixture into a mold for curing and molding to obtain the flexible aerogel material.
2. The preparation method according to claim 1, characterized in that: In step (1), the particle size of the aerogel powder particles is 1 μm to 100 μm.
3. The preparation method according to claim 1 or 2, characterized in that: In step (1), the length of the fiber is 0.1 mm to 10 mm, and the diameter is 10 μm to 100 μm; Preferably, the weight ratio of the aerogel powder particles to the fibers in the mixture is 1:0.2-5.
4. The preparation method according to any one of claims 1 to 3, characterized in that: In step (2), the weight ratio of the organic resin glue, the diluent solvent and the curing agent is 1:10-100:0.01-0.
50.
5. The preparation method according to claim 1, characterized in that: In step (2), the organic resin glue is polyurethane glue or polyacrylate glue; The dilution solvent is selected from one of acetone, butanone, toluene and cyclohexanone; The curing agent is selected from one of triethylamine, stannous octoate and acrylic resin.
6. The preparation method according to any one of claims 1 to 5, characterized in that In step (2): The viscosity of the impregnation liquid is 100 mPa·s to 20000 mPa·s; Preferably, the viscosity of the impregnation liquid is 100 mPa·s to 1000 mPa·s; It is also preferred that the viscosity of the impregnation liquid is 1000mPa·s to 10000mPa·s; In addition, preferably, the viscosity of the impregnation liquid is 10000 mPa·s to 20000 mPa·s.
7. The preparation method according to any one of claims 1 to 6, characterized in that: In step (3), the weight ratio of the mixed material to the impregnating liquid is 1:5 to 20; In step (3), the stirring speed is 30 rpm to 200 rpm, and the stirring temperature is 15° C. to 35° C.
8. The preparation method according to any one of claims 1 to 7, characterized in that In step (4): The curing temperature of the curing is 40°C to 80°C, and the curing time is 4h to 24h; Preferably, the curing is performed with the assistance of microwaves.
9. The flexible aerogel material obtained by the preparation method according to any one of claims 1 to 8.
10. Use of the aerogel material obtained by the method according to any one of claims 1 to 8 or the aerogel material according to claim 9 in heat-resistant materials or heat-insulating materials, especially heat-resistant materials or heat-insulating materials for manufacturing special-shaped components.
Citation Information
Patent Citations
An aerogel corrosion-resistant and heat-insulating flexible board and its manufacturing method
CN113510978B
Composite SiO2 aerogel heat-insulation felt pad and preparation method
CN103922643A
Aerogel complex fiber thermal insulation material and preparation method thereof
CN104047368A
Low-cost aerogel thermal insulation material, as well as preparation method and application thereof
CN108503327A
Aerogel mat and aerogel mat manufacturing method using porous silica aerogel powder
KR1020120043329A